EMAS position statement: Predictors of premature and early natural menopause. (May 2019) - Mishra, Gita D.; Chung, Hsin-Fang; Cano, Antonio; Chedraui, Peter; Goulis, Dimitrios G.; Lopes, Patrice; Mueck, Alfred; Rees, Margaret; Senturk, Levent M.; Simoncini, Tommaso; Stevenson, John C.; Stute, Petra; et al.
Highlights: A family history of premature or early menopause, being a multiple-birth child and some specific genetic variants are strong genetic predictors–. Early menarche, nulliparity, cigarette smoking and being underweight are strong reproductive and lifestyle predictors. Current clinical guidelines recommend early initiation of hormone therapy and continued use until the average age at menopause (50–52 years). Ethnicity-specific age at menopause should be considered in the assessment for the timing of cessation of hormone therapy. Abstract: Introduction: While the associations of genetic, reproductive and environmental factors with the timing of natural menopause have been extensively investigated, few epidemiological studies have specifically examined their association with premature (<40 years) or early natural menopause (40–45 years). Aim: The aim of this position statement is to provide evidence on the predictors of premature and early natural menopause, as well as recommendations for the management of premature and early menopause and future research. Materials and methods: Literature review and consensus of expert opinion. Results and conclusions: Strong genetic predictors of premature and early menopause include a family history of premature or early menopause, being a child of a multiple pregnancy and some specific genetic variants. Women with early menarche and nulliparity or low parity are also at a higher risk of experiencing premature or early menopause. Cigarette smoking (with a strong dose–response effect) and being underweight have been consistently associated with premature and early menopause. Current guidelines for the management of premature and early menopause mainly focus on early initiation of hormone therapy (HT) and continued treatment until the woman reaches the average age at menopause (50–52 years). We suggest that clinicians and health professionals consider the age at menopause of the relevant region or ethnic group as part of the assessment for the timing of HT cessation. In addition, there should be early monitoring of women with a family history of early menopause, who are a child of a multiple pregnancy, or who have had early menarche (especially those who have had no children). As part of preventive health strategies, women should be encouraged to quit smoking (preferably before the age of 30 years) and maintain optimal weight in order to reduce their risk of premature or early menopause.